Histone Modifications: Epigenetic Mediators of Environmental Exposure Memory - Camacho, Jessica (Epigenet Insights, 2018)
How organisms retain a memory of ancestral environmental exposure is a phenomenon that is still poorly understood. Recently published work by our group and others, regarding environmentally induced transgenerational effects, have identified an array of mechanisms, with a particular focus on histone modifications, that shed some light on the underlying epigenetic processes driving long-term generational effects.